STRATEGI PERENCANAAN PEMBANGUNAN INDUSTRI BERBASIS PRODUK UNGGULAN DAERAH, STUDI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN BLITAR - Eyuda Angga Pradigda (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This paper aims to determine the superior product of Blitar Regency along with its development strategy, in conjunction with the preparation of the Regional Industrial Development Plan. In determining the products featured in 2 stages, namely the identification of seed processing industry subsector analysis shiftshare, later identified superior products based seed processing industry subsectors. In determining the priority flagship product alternatives using Analytical Hierarchy Process (AHP). Based on the analysis shiftshare and AHP, coconut shell crafts determined as a superior product of Blitar. Furthermore, the preparation of the product development strategy using SWOT analysis.